The Role of Adaptive Innovation in Sustainable Competitiveness: Evidence from Private Higher Education Institutions' Response to Digital Disruption on Student Retention and Institutional Reputation - Yenny Marthalena; M. Yusuf S. Barusman; Andala R.P. Barusman; Defrizal Defrizal; Sunarmi Sunarmi; Yuni Astini (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Private higher education institutions face increasing pressure from digital disruption, competition, and changing stakeholder expectations. However, digital transformation does not automatically lead to innovation outcomes. This study examines the roles of digital disruption, dynamic capabilities, and organizational ambidexterity in developing adaptive innovation and its impact on student retention, institutional reputation, and sustainable competitive advantage. Research Gap: Previous studies have largely focused on technology adoption, digital learning platforms, and technological readiness, providing limited explanation of how digital disruption is transformed into adaptive innovation and institutional outcomes. The organizational mechanisms underlying adaptive innovation remain insufficiently integrated, with dynamic capabilities and organizational ambidexterity often examined separately rather than as interconnected capability mechanisms. Novelty: This study develops an integrated framework linking digital disruption, dynamic capabilities, and organizational ambidexterity with adaptive innovation, and examines how adaptive innovation contributes to student retention, institutional reputation, and sustainable competitive advantage in private higher education institutions, extending Dynamic Capabilities Theory into the higher education context. Method: A quantitative explanatory design using a cross-sectional survey was employed. Data were collected from 316 academic and managerial respondents across 77 private higher education institutions in the LLDIKTI Region II area of Indonesia. The proposed model was analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4.0, including measurement model assessment, structural model evaluation, effect size analysis, and predictive assessment. Results: The findings show that dynamic capabilities strongly influence adaptive innovation (β=0.802, p<0.001), followed by organizational ambidexterity (β=0.241, p<0.001). Adaptive innovation positively affects student retention (β=0.741, p<0.001) and institutional reputation (β=0.916, p<0.001), while institutional reputation enhances sustainable competitive advantage (β=0.744, p<0.001). Digital disruption does not significantly influence adaptive innovation (β=-0.036, p=0.054), indicating that technology pressure alone is insufficient to generate innovation without organizational capabilities. The model explains 93.3% of the variance in adaptive innovation. Conclusion: Adaptive innovation in private higher education institutions is primarily capability-driven rather than technology-driven. The study extends Dynamic Capabilities Theory by demonstrating that organizational capabilities are essential for transforming digital challenges into innovation outcomes and sustainable competitiveness.